The effect of modified alternate day calorie restriction (MACR) on non-alcoholic fatty liver disease (NAFLD) - Johari, Muhammad Izzad (2017)
Background: Non-alcoholic fatty liver diseases are an important cause of morbidity and mortality due to adverse cardiovascular outcomes and also liver-related complications. Currently, there is no approved therapy for non-alcoholic fatty liver diseases; weight reduction is typically recommended. Modified alternate day calorie restriction is more feasible to the patient compared to daily calorie restriction; however, no trials have been done in non-alcoholic fatty liver diseases patients focusing on changes in liver fibrosis and steatosis. Objectives: The aim of this study is to evaluate the effect of modified alternate day calorie restriction on the changes in liver steatosis and fibrosis, anthropometry as well as biochemical parameters in non-alcoholic fatty liver diseases patients after 8 weeks of modified alternate day calorie restriction.Methods: We performed a prospective study involving adult gastroenterology patients with non-alcoholic fatty liver disease from August 2015 to July 2016 in Hospital Universiti Sains Malaysia. Results: A total of 105 patients were screened, 41 consented but 11 withdrew and 30 participants (mean age 43.9 years, BMI 31.5kg/m2, males 70%, diabetes 53%) completed the study. With 8 week MACR, significant reductions were observed of grading of liver steatosis (40% reduction in those with moderate steatosis, P=0.001), SWE (mean difference 0.9, P=0.001), BMI (mean difference 0.6 kg/m2, P=0.003), glucose (median difference 0.3 mmol/L, P=0.01), ALT (median difference 20.5 U/L, P=0.001) and AST (median difference 9 U/L, P=0.002) Conclusion: In summary, the results indicate that modified alternate day calorie restriction appear to be an effective diet strategy to help reducing the risk of progression for non-alcoholic fatty liver diseases especially in patients with moderate steatosis and mild fibrosis.